Concentrations of MMP-9 and TIMP-1 in lip tissue and their impact on cleft lip surgery healing - Blaha, Karel; Borsky, Jiri; Kasparova, Magdalena; Steklacova, Anna; Zajickova, Veronika; Pechova, Marta; Matejova, Radka; Kotaska, Karel; Dostalova, Tatjana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
AIM: To compare aspects of wound healing after cleft lip surgery performed within one week of age and wound healing after surgery performed within 2 - 4 months of age, especially concentrations of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinases-1 (TIMP-1) in tissue removed during surgery. METHODS: 34 tissue samples (26 boys and 8 girls) were removed during surgery within one week of age (n=19) or within 2 - 4 months of age (n=15). Tissue samples were separated into epidermis, dermis and mucous membrane. Proteins were extracted in cacodylic buffer for 24 h at a temperature 2 - 8 ºC. Total protein concentrations were examined using a modification of the Lowry method. Samples were examined using ELISA kit Amersham Biotrak Activity Assay (GE Healthcare UK) for detection of MMP-9 and TIMP-1 concentrations. RESULTS: MMP-9: early surgery - epidermis 2.168 ± 3.303 μg/g of protein (mean ± SD), dermis 1.251 ± 1.848 µg/g, 2 - 4 months surgery - epidermis 0.347 ± 0.212 μg/g, dermis 0.555 ± 0.276 µg/g. TIMP-1: early surgery - epidermis 1.762 ± 2.162 μg/g, dermis 1.628 ± 0.822 µg/g, mucous membrane 2.066 ± 1.717 µg/g, 2 - 4 months surgery - epidermis 1.881 ± 2.810 μg/g, dermis 3.117 ± 1.540 µg/g, mucous membrane 4.833 ± 6.550 µg/g. CONCLUSIONS: There were no significant differences in concentrations of protein MMP-9 in epidermis and dermis and TIMP-1 in epidermis and mucous membrane according to time of surgery. Significantly decreased levels of TIMP-1 in dermis were found in samples obtained from early surgery compared to levels in samples obtained from 2 - 4 months surgery.
Keywords: rozštěp rtu; Wound Healing; ret; kojenec; mužské pohlaví; Cleft Lip; Infant; hojení ran; Lip; Infant, Newborn; Matrix Metalloproteinase 9; ženské pohlaví; novorozenec; tkáňový inhibitor metaloproteinasy 1; Humans; Tissue Inhibitor of Metalloproteinase-1; matrixová metaloproteinasa 9; Female; lidé; Male